Avoiding a Global Carbon Crisis: Learning from the Financial Crisis. (25th October 2013) - Shrivastava, Paul; Busch, Timo
Abstract The global financial crisis originated in the subprime mortgage market in the United States in 2008 and its effects spread to all of the world's major financial markets. Only governmental programs and subsidies have prevented an outright crash of the world economy. What can the financial crisis teach us about the impending carbon crisis? What is needed to move the global economy toward sustainability, using renewable energy regimes, and low carbon consumption and production? This paper provides a nontechnological response to these questions by highlighting six key sociocultural lessons and suggesting two key recommendations in how to overcome the current carbon lock‐in. Firms should establish proactive climate strategies. Policymakers can facilitate this by developing farsighted governance mechanisms and setting the right incentives and boundary conditions. We conclude that a mix of both is required to prevent the global carbon crisis from becoming a reality. © 2013 Wiley Periodicals, Inc.